2018
DOI: 10.1080/09540121.2018.1470306
|View full text |Cite
|
Sign up to set email alerts
|

The high incidence of late presenters for HIV/AIDS infection in the Lodz province, Poland in the years 2009–2016: we are still far from the UNAIDS 90% target

Abstract: The present study retrospectively analyses the prevalence of late diagnosis in patients with newly-diagnosed HIV infection in Lodz, Poland from January 2009 to December 2016, and assesses the predictive factors associated with late presenters. Late presentation is defined as a diagnosis of HIV with a CD4 count<350 cells/μL, or the occurrence of an AIDS- defining event, regardless of the CD4 cell count. Two hundred and fifty-nine (62.86%) patients were late presenters, 178 of whom (68.72%) were advanced late pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…Furthermore, according to other studies in Poland and the Netherlands, males were also more prevalent in the late presenters’ population. These results are consistent with our study [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, according to other studies in Poland and the Netherlands, males were also more prevalent in the late presenters’ population. These results are consistent with our study [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…The results from previous studies showed statistically significant correlation between late presentation and HIV exposure category [6,16,17]. While we did not find this significant correlation in our logistic regression analysis, we did find it in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 83%
“…However, data from a smaller single‐centre study in Poland showed a very high (63%) incidence of late presentation for HIV infection. Similarly, older individuals and those with a history of active drug use and the heterosexual route of transmission were more likely to present late than MSM . The decrease in the frequency of individuals presenting late and with advanced HIV disease may be associated with greater awareness and a higher frequency of testing , and is reflected in the increasing number of individuals entering care with asymptomatic infection, especially in the MSM population (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…This has been associated with improved prognosis and a decrease in mortality among HIV‐infected patients. Delayed HIV diagnosis and late care entry, linked to late presentation either with diagnosed AIDS or with low CD4 counts, remain major challenges for the control of the HIV/AIDS epidemic, with single‐centre data indicating that 50 to 63% of individuals were linked to care with either AIDS or a CD4 count < 350 cells/μL, despite expansion of test and treat efforts in Poland .…”
Section: Introductionmentioning
confidence: 99%